Synthesis, Characterization and Catalytic Performance of Ceria-Supported Cobalt Catalyst for Methane Dry Reforming To Syngas - Ayodele, Bamidele V.; Nor Shahirah, Mohd Nasir; Khan, Maksudur R.; Cheng, C. K. (Universiti Kebangsaan Malaysia, 2017)
In this study the synthesis, characterization and catalytic performance of CeO2 (Ceria) supported Co catalyst was investigated. First, the ceria was synthesized by direct thermal decomposition of Ce(NO3)3.6H2O and subsequently impregnated with 20 wt.% Co using aqueous solution of Co(NO3)2.6H2O as a precursor. The synthesized catalyst was characterized using TGA, N2-adsorption-desorption, X-ray Diffractometry (XRD), Field Emission Scanning Electron Microscope (FESEM-EDX), and Fourier Transformation Infrared (FTIR). The catalytic property of the ceria-supported cobalt catalyst was tested in methane dry reforming using a stainless steel fixed bed reactor. The dry reforming reaction was performed at the temperature range of 923-1023 K under a controlled atmospheric pressure and constant gas hourly space velocity (GHSV) of 30000 h-1. The effects of reactant (CH4 and CO2) feed ratio was investigated on reactants conversion, product yields, and selectivity. The ceria-supported cobalt catalyst recorded highest catalytic activity at a CH4: CO2 ratio of 0.9 and temperature of 1023 K. The highest values of 79.5% and 87.6% were recorded for the CH4 and CO2 conversions respectively. Furthermore, highest yields of 41.98% and 39.76%, as well as selectivity of 19.56% and 20.72%, were obtained for H2 and CO respectively. Syngas ratio of 0.90 was obtained from the dry reforming of methane, making it suitable as feedstock for Fischer-Tropsch synthesis (FTS).